(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To evaluate functional outcome of the anterior interosseous nerve transfer to the motor branch of the ulnar nerve for cases of high ulnar nerve injuries Methods: This descriptive study was conducted in Hand and Upper Limb Surgery (HULS) CMH Lahore Medical College Pakistan from 21st July 2016 to 21st August 2018. A total of 13 patients (10 males, 03 females), mean age 32years(range 18 to 42) with injury to the ulnar nerve(high) were treated with anterior interosseous nerve(AIN) transfer to the motor branch of ulnar nerve. Functional outcome was evaluated clinically preoperatively, immediately postoperatively and 03 to 06 month follow up to evaluate motor functional grading system. Results: In high ulnar nerve injury in whom anterior interosseous nerve was transferred all cases showed good outcomes (M3 to M4 by motor functional grading system) with mean initial recovery period of 3.5 months Conclusion: Treatment of high ulnar nerve injury with transfer of the anterior interosseous nerve to the motor branch of the ulnar nerve results in early near normal intrinsic recovery and restoration of hand functions.